RPE-Directed Gene Therapy Improves Mitochondrial Function in Murine Dry AMD Models - Humphries, Marian; Farrar, Gwyneth; Humphries, Peter; Kenna, Paul (My University, 2023)
Age-related macular degeneration (AMD) is the most common cause of blindness in the aged population. However, to date there is no effective treatment for the dry form of the disease, representing 85–90% of cases. AMD is an immensely complex disease which affects, amongst others, both retinal pigment epithelium (RPE) and photoreceptor cells and leads to the progressive loss of central vision. Mitochondrial dysfunction in both RPE and photoreceptor cells is emerging as a key player in the disease. There are indications that during disease progression, the RPE is first impaired and RPE dysfunction in turn leads to subsequent photoreceptor cell degeneration; however, the exact sequence of events has not as yet been fully determined. We recently showed that AAV delivery of an optimised NADH-ubiquinone oxidoreductase (NDI1) gene, a nuclear-encoded complex 1 equivalent from S. cerevisiae, expressed from a general promoter, provided robust benefit in a variety of murine and cellular models of dry AMD; this was the first study employing a gene therapy to directly boost mitochondrial function, providing functional benefit in vivo. However, use of a restricted RPE specific promoter to drive expression of the gene therapy enables exploration of the optimal target retinal cell type for dry AMD therapies. Furthermore, such restricted transgene expression could reduce potential off-target effects, possibly improving the safety profile of the therapy. Therefore, in the current study, we interrogate whether expression of the gene therapy from the RPE-specific promoter, Vitelliform macular dystrophy 2 (VMD2), might be sufficient to rescue dry AMD models
PUBLISHED
cited By 0
Keywords: AMD models; gene therapy; retina; BEST1; Mitochondria; Promoter; Age-related macular degeneration; Retina; AAV; RPE; VMD2